1999
DOI: 10.1016/s0304-3959(99)00059-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between a genetic predisposition to hypertension, blood pressure levels and pain sensitivity

Abstract: Pain sensitivity is correlated to blood pressure levels whereas the parental history of hypertension per se does not affect the pain perception pattern. Thus, the degree of blood pressure elevation, more than a genetic predisposition to hypertension may influence the mechanisms leading to hypalgesia in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…Specifically, reduced sensitivity to a variet5r of naturally occurring and laboratory pain stimuli has been observed in individuals with hypertension [16][17][18][22][23][24]39 -42,47,571, high-normal blood pressure {2,9, '17,27,29,33,46), and a family history of hypertension. [1,5,10,11,13,30,33].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, reduced sensitivity to a variet5r of naturally occurring and laboratory pain stimuli has been observed in individuals with hypertension [16][17][18][22][23][24]39 -42,47,571, high-normal blood pressure {2,9, '17,27,29,33,46), and a family history of hypertension. [1,5,10,11,13,30,33].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that, depending on the intensity of the external stimulus, touch and pain receptors may activate simultaneously 14 ; therefore, some prior research focused specifically on pain assessment may help explain the findings of the present study. Several studies have suggested that normotensive people are more sensitive to pain [21][22][23] and experience reductions in pain sensation after resistance training and aerobic exercise. [10][11][12] Koltyn and Arbogast 12 assessed the influence of resistance training on pain threshold and pain scores in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (Guasti et al, 1995;Guasti et al, 1999), a TAKEDA TM2421 (A and D Co) set to take one measure every 15 min for a 24-hour period was used. This instrument has a combined auscultatory and oscillometric method to minimize errors.…”
Section: Twenty-four Hour Ambulatory Blood Pressurementioning
confidence: 99%
“…The test quality was good (N80% valid measurements) in all the subjects. A computerized program did the reading and editing of the data (Guasti et al, 1995;Guasti et al, 1999). The 24-hour values of systolic and diastolic mean blood pressures were computed.…”
Section: Twenty-four Hour Ambulatory Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation